Pengaruh Kebijakan Perpajakan pada Perencanaan Pajak dengan Sanksi Administrasi sebagai Pemoderasi - I Putu Edy Arizona (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
This study aims to determine and obtain empirical evidence of the effect of tax policy on individual taxpayer tax planning, with tax sanctions as a moderating variable at the South Badung Tax Service Office. The research population amounted to 77,248 taxpayers, and we obtained a sample of 100 taxpayers. The analysis technique used in this research is moderated regression analysis (MRA). The results showed that tax policy had a positive effect on tax planning, and administrative sanctions were unable to moderate tax policy on tax planning.